Avian flu: the creation of expectations in the interplay between science and the media - Nerlich, Brigitte; Halliday, Christopher (2007)
This paper examines the emerging cultural patterns and interpretative repertoires in reports of an impending pandemic of avian flu in the UK mass media and scientific journals at the beginning of 2005, paying particular attention to metaphors, pragmatic markers ('risk signals'), symbolic dates and scare statistics used by scientists and the media to create expectations and elicit actions. This study complements other work on the metaphorical framing of infectious disease, such as foot and mouth disease and SARS, tries to link it to developments in the sociology of expectations and applies insights from pragmatics both to the sociology of metaphor and the sociology of expectations.